Covid-19 #Takeresponsibility: A Multimodal Discourse Analysis of Select NCDC’s Online Public Health Advertising Campaign - Adetutu Aragbuwa; Victor O. Adejumo (Universitas Sanata Dharma, 2021)
This article examines the Nigerian Center for Disease Control’s (henceforth, NCDC) Covid-19 #TakeResponsibility online public health advertising campaign. This is with a view to exploring how the representational, interactive and compositional resources are realized in these advertising visuals as well as their communicative functions. Forty purposively selected data samples, which were subjected to qualitative analysis, are examined from a multimodal discourse analytical approach. The analysis reveals that the narrative, transactive, action, offer, and the frontal resources, among others, are realized in the adverts. These resources interactively perform the directive, informative, reinforcing, preventive, cautionary and collective functions. Thus, the representational, interactive and compositional resources deployed in the NCDC’s Covid-19 #TakeResponsibility online visuals discursively cohere as multimodal public health campaign strategies geared towards sensitizing the Nigerian populace on the safety guidelines to adhere to in containing the spread of Covid-19 in Nigeria.